Influence of cell culture transplantation on islet cell of the pancreas condition and on blood glucose level at experimental pancreatic diabetes of animals - Ковпак, В. В.; Ковпак, О. С. (Scientific Progress & Innovations, 2017)
The article describes the influence of various cell cultures (pancreas, bone marrow, adipose tissue) on the clinical course of experimental pancreatic diabetes of rats. It is found out that the optimal method of cell material injection is its transplantation under the pancreatic capsule. The study of islet cell condition under injecting various cell cultures in the setting of pancreatic diabetes showed that all of them produce a positive therapeutic effect in the treatment of the this pathology. The obtained data is testified by the growth of a general volume of islet tissue of recipient animals (compared to a control set); this in its turn results in the decrease of blood serum glucose level.